1992
DOI: 10.1016/0735-1097(92)90050-w
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preoperative pulmonary artery pressure on mortality after heart transplantation: Testing of potential reversibility of pulmonary hypertension with nitroprusside is useful in defining a high risk group

Abstract: Patients with pulmonary hypertension are at risk of developing fatal right heart failure after heart transplantation. To evaluate this risk potential, candidates for heart transplantation are screened by measuring rest right heart pressures and the response to nitroprusside. To test the validity of this approach, the influence of pretransplantation right heart catheterization data on outcome after transplantation was analyzed in 293 of 301 consecutive patients. Patients with a pulmonary vascular resistance gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
232
0
12

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(248 citation statements)
references
References 11 publications
4
232
0
12
Order By: Relevance
“…Pulmoner vasküler direncin farmakolojik yoldan (örn. i.v nitroprusid ile) düşürülmesi durumunda, bu risk azaltılabilir (26).…”
Section: Tanıunclassified
“…Pulmoner vasküler direncin farmakolojik yoldan (örn. i.v nitroprusid ile) düşürülmesi durumunda, bu risk azaltılabilir (26).…”
Section: Tanıunclassified
“…with i.v. nitroprusside) this risk may be reduced [231]. The absence of consensus on a standardised protocol leads to the use of various agents for testing the responsiveness of the pulmonary circulation, including inotropic agents, vasodilators, prostanoids, NO and phosphodiesterase type-5 inhibitors.…”
Section: Esc/ers Guidelines N Galiè Et Almentioning
confidence: 99%
“…Pulmonary hypertension (PH) is recognised in 50-60% of patients referred for heart transplantation (HTx) and has, according to some authors, a significant influence on patient's prognosis. Contrary to that, some authors have reported that patients with chronic HF have poor prognosis and that PH has no further influence on prognosis at this stage of disease [9,10].…”
Section: Introductionmentioning
confidence: 87%